Dispersive admicelle solid‐phase extraction based on sodium dodecyl sulfate coated Fe3O4 nanoparticles for the selective adsorption of three alkaloids in Gegen‐Qinlian oral liquid before high‐performance liquid chromatography. Issue 23 (30th October 2017) - Shi, Zhihong; Xu, Dan; Zhao, Xuan; Li, Xinghong; Shen, Huimin; Yang, Bing; Zhang, Hongyi
Abstract: A novel dispersive admicelle solid‐phase extraction method based on sodium dodecyl sulfate‐coated Fe3 O4 nanoparticles was developed for the selective adsorption of berberine, coptisine, and palmatine in Gegen‐Qinlian oral liquid before high‐performance liquid chromatography. Fe3 O4 nanoparticles were synthesized by a chemical coprecipitation method and characterized by using transmission electron microscopy. Under acidic conditions, the surface of Fe3 O4 nanoparticles was coated with sodium dodecyl sulfate to form a nano‐sized admicelle magnetic sorbent. Owing to electrostatic interaction, the alkaloids were adsorbed onto the oppositely charged admicelle magnetic nanoparticles. The quick separation of the analyte‐adsorbed nanoparticles from the sample solution was performed by using Nd‐Fe‐B magnet. Best extraction efficiency was achieved under the following conditions: 800 μL Fe3 O4 nanoparticles suspension (20 mg/mL), 150 μL sodium dodecyl sulfate solution (10 mg/mL), pH 2, and vortexing time 2 min for the extraction of alkaloids from 10 mL of diluted sample. Four hundred microliters of methanol was used to desorb the alkaloids by vortexing for 1 min. Satisfactory extraction recoveries were obtained in the range of 85.9–120.3%, relative standard deviations for intra‐ and interday precisions were less than 6.3 and 10.0%, respectively. Finally, the established method was successfully applied to analyze the alkaloids in two batches of Gegen‐Qinlian oral liquids.